Integrating Islamic Values and Financial Strategy The Role of Shariah-Based Financial Management in Enhancing the Performance of Muslim MSMEs - Suginam, Suginam; Pamungkas, Bambang; Rahayu, Sri; Hashim, Noraini (Institut Bisnis dan Informatika Kesatuan, 2025)
Muslim micro, small, and medium enterprises (MSMEs) in Indonesia hold substantial potential in strengthening the national economy. However, they face major challenges in implementing strategic financial management that aligns with Islamic principles. The core issues include low levels of Shariah financial literacy, weak adherence to Islamic financial ethics, and suboptimal application of Shariah-compliant strategic financial management. This study investigates the impact of Shariah-Based Financial Literacy (SBFL), Shariah Compliance Behavior (SCB), and Strategic Financial Management (SFM) on the performance of Muslim MSMEs. Furthermore, it explores the moderating role of Islamic Entrepreneurial Orientation (IEO) in these relationships. Using a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, data was collected from 100 Muslim MSME entrepreneurs in Indonesia. The findings reveal that all three independent variables significantly and positively affect business performance. Moreover, IEO significantly moderates these effects, indicating that Islamic entrepreneurial values reinforce the impact of Shariah-based financial management on business outcomes. The model demonstrates a strong explanatory power with an R-square value of 0.727 and a predictive relevance (Q-square) of 0.586. This study recommends promoting Shariah financial literacy, strengthening Islamic business conduct, and fostering Islamic entrepreneurial orientation as part of a sustainable empowerment strategy for Muslim MSMEs. Keywords: Shariah Finance, Muslim MSMEs, Financial Literacy, Shariah Compliance, Islamic Entrepreneurship